Capitalism without democracy : the private sector in contemporary China - Tsai, Kellee S. (Cornell University Press, 2007)
Based on years of research, hundreds of field interviews, and a sweeping nationwide survey of private entrepreneurs, this text explodes the conventional wisdom about the relationship between economic liberalism and political freedom.